2022
DOI: 10.1177/03000605221137470
|View full text |Cite
|
Sign up to set email alerts
|

Healthy adults with Streptococcus pneumoniae meningitis and Streptococcus pneumoniae subdural abscess: two case reports and a literature review

Abstract: We present the cases of two otherwise healthy adults, one with meningitis and another with a subdural abscess, with both conditions attributable to Streptococcus pneumoniae. A 31-year-old man was admitted with a 3-day history of fever, headache, and vomiting. Physical examination revealed intermittent confusion, irritability, and neck stiffness. Cerebrospinal fluid (CSF) culture was positive for S. pneumoniae. Contrast-enhanced magnetic resonance imaging (C-MRI) revealed multiple small lesions on the bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Acute subdural abscess caused by brain abscess rupture is rare and difficult to diagnose, and is easily confused with glioma, metastatic tumor, and subdural effusion. 5 If coma, chills, high fever, convulsions, and even gongs occur suddenly on the basis of clear intracranial space occupying lesions, the possibility of brain abscess rupture should be highly suspected. 4 The disease can evolve rapidly, including decreased consciousness level, focal nerve defect, cranial nerve paralysis, vomiting, and even infectious shock.…”
Section: Discussionmentioning
confidence: 99%
“…Acute subdural abscess caused by brain abscess rupture is rare and difficult to diagnose, and is easily confused with glioma, metastatic tumor, and subdural effusion. 5 If coma, chills, high fever, convulsions, and even gongs occur suddenly on the basis of clear intracranial space occupying lesions, the possibility of brain abscess rupture should be highly suspected. 4 The disease can evolve rapidly, including decreased consciousness level, focal nerve defect, cranial nerve paralysis, vomiting, and even infectious shock.…”
Section: Discussionmentioning
confidence: 99%
“…Meningoencephalitis due to Streptococcus pneumoniae may result in severe postinfection sequelae, with fatality rates of between 19 and 37%. SME occurs most commonly in association with head trauma, chronic sinusitis, and neurosurgical procedures [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis and antimicrobial intervention are essential for reducing mortality and disability associated with BME. While some case reports have demonstrated that S. pneumoniae may cause subdural abscesses, the underlying mechanism is poorly understood [ 1 , 8 ]. The authors’ bedside assessment of saccadic velocity [ 9 ] was helpful in diagnosing a bedridden, visually and hearing impaired patient with WEBINO and bilateral third-nerve palsies.…”
Section: Introductionmentioning
confidence: 99%